Efficiency of a Solar Hydronic Space Heating System under the Algerian Climate - Zeghib, I.; Chaker, A. (Engineering, Technology & Applied Science Research, 2016)
Hydronic heating systems supplied by renewable energy sources are one of the main solutions for substituting fossil fuel and natural gas consumption. This paper presents the development of modeling and analysis of a solar hydronic heating system in an existing single-family house built in 1990’s heated by low-temperature radiators. The simulation has been used to study the potential of using this system under climatic conditions in Algeria. And for this purpose, a component based on the simulation model for the thermal behavior of each component of the system are carried out in order to evaluate the economic performance for this system. The system is compared, with a conventional high-temperature boiler system. The results indicated that single-family houses could be heated with solar hydronic heating and provided an acceptable level of thermal comfort in the room with 22°C, according to the results of the analysis, the solar energy covers only 20.8% of the total energy consumption in a single-family house. Furthermore, the thermal performance of the heating conventional system can be largely improved up to 15%.